2017
DOI: 10.1177/1948550617697177
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence Tests

Abstract: Scientists should be able to provide support for the absence of a meaningful effect. Currently, researchers often incorrectly conclude an effect is absent based a nonsignificant result. A widely recommended approach within a frequentist framework is to test for equivalence. In equivalence tests, such as the two one-sided tests (TOST) procedure discussed in this article, an upper and lower equivalence bound is specified based on the smallest effect size of interest. The TOST procedure can be used to statistical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
577
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,358 publications
(652 citation statements)
references
References 41 publications
7
577
1
6
Order By: Relevance
“…A TOST procedure indicated that baseline reaction times were equivalent in both conditions (i.e. the observed effect size of d z = -0.02 was within the equivalent bounds of a moderate effect size of d z = -0.4 and 0.4; t(31)=2.15, p=0.02 [20]). The baseline RTs (Block 1) were then subtracted from each subsequent block to create a ΔRT value for each of Blocks 2-4 ( Figure 3B).…”
Section: Reaction Timesmentioning
confidence: 98%
“…A TOST procedure indicated that baseline reaction times were equivalent in both conditions (i.e. the observed effect size of d z = -0.02 was within the equivalent bounds of a moderate effect size of d z = -0.4 and 0.4; t(31)=2.15, p=0.02 [20]). The baseline RTs (Block 1) were then subtracted from each subsequent block to create a ΔRT value for each of Blocks 2-4 ( Figure 3B).…”
Section: Reaction Timesmentioning
confidence: 98%
“…Two one-sided t-tests (TOSTs) evaluated equivalence between each pairwise comparison [52] as implemented in the `equivalence` package in R. TOSTs require an upper and lower bound effect size. Due to increased sample sizes required to conduct TOSTs [52], effect sizes conventionally considered to be medium magnitude were first examined, setting our equivalence boundary at d = -.5 and .5, respectively. A follow-up analysis used an effect size boundary from d = -.3 to .3 to compare Occasional and Non-Users (Frequent User comparisons were not conducted at this boundary due to limited power).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In particular, participants who played the first-price auction against a computer who stopped bidding at 46cents drive this result, as they were bidding significantly more (M = 59.9, SEM = 3.7) than participants who played the first-price auction against a computer player who stopped bidding at 50 cents (M = 48.8, SEM = 4.2, t(206) = 1.99, p = .048, d = 0.27). Even in this case, we can reject the hypothesis that direct experience in a competitive situation without the escalation aspect would reduce escalation by 1 cent or more (p = .04, following the TOST procedure,Lakens, 2017).Supporting Hypothesis 4, participants with indirect experience of vicariously learning the consequences of a competitive escalation situation escalated less (M = 34.0, SEM = 2.29) in a subsequent competitive escalation situation than other participants without such indirect experience (t(393) = 2.47, p = .01, d = 0.24). Supporting Hypothesis 5, participants who mentally simulated how the competitive escalation situation would unfold and set themselves a limit did not escalate significantly less in a subsequent competitive escalation situation (M = 43.0, SEM = 2.42) than participants without such an indirect…”
mentioning
confidence: 68%